Towards low-carbon ammonia: simulation and economic evaluation of blue ammonia with carbon utilization - Vibianti Dwi Pratiwi; Sukmawati Kunup; Nada Rahma Aulia; Helmi Sayid Hasan; Jono Suhartono (Universitas Mercu Buana, 2026)
The proposed blue ammonia production considers technical, environmental, and economic aspects. The design of the blue ammonia using CCUS (Carbon Capture, Utilization, and Storage) technology in this study contributes to reducing carbon emissions and providing a more environmentally friendly ammonia supply in East Java, Indonesia, due to the availability of raw materials and geological storage locations for CO2 storage. Technically, the blue ammonia production was simulated with Aspen Hysys V.14.0. uses the Kellogg process, where the ammonia converter operates at a temperature of 437.60 °C and a pressure of 141.9 bar. From the environmental aspect, as much as 68.34 tons/h of ammonia produced produces CO2 71.36 tons/h, which is a total emission of 1.06 tons CO2/ tons NH3. In this study, CO2 delivery with a pipe length of 85 km (ID:539.8mm; OD: 558.7mm) was simulated using default parameters in Aspen Hysys V.14.0. In economic calculations from APEA (Aspen Process Economic Analyzer), the manufacture of blue ammonia designed in this study is very large, with a TAC (Total Annual Cost) of 82.25x106/year and an LCOA (Levelized Cost of Ammonia) of 93.28x108/ tons NH3. This study demonstrates the integration of CCUS technology into ammonia production, resulting in a reduction of CO₂ emissions by 1.06 tons CO₂ per ton of ammonia produced. The proposed system provides a practical approach for improving the environmental sustainability of industrial chemical processes.